Reckoning with conservation violence on indigenous territories: possibilities and limitations of a transitional justice response - Luoma, Colin (International journal of transitional justice, 2023)
This article reflects on the merits of applying transitional justice to wrongs caused by the creation and enforcement of protected areas on Indigenous Peoples’ territories, referred to herein as ‘conservation violence.’ Conservation violence commonly infringes on an interrelated set of human rights, constituting a principal threat to both Indigenous Peoples and the environment. This wrongdoing has not been adequately scrutinized in transitional justice discourse, despite the field’s recent expansion into areas of Indigenous and environmental harm. This article argues there are sound conceptual and pragmatic reasons for transitional justice to engage with conservation violence, with potential benefits flowing to both Indigenous Peoples and nature. Yet, it is unlikely to deliver what Indigenous Peoples principally demand, namely restitution of their lands, territories and resources. This raises concerns regarding the suitability of applying conventional transitional justice in this context and dictates that any process should be approached modestly, cautiously and in complement to broader, long-term reforms aimed at land restitution and decolonization.